2020
DOI: 10.1155/2020/6861416
|View full text |Cite
|
Sign up to set email alerts
|

Using YouTube to Learn Anatomy: Perspectives of Jordanian Medical Students

Abstract: Purpose. The study is aimed at exploring the popularity, impact, and usefulness of using YouTube in learning anatomy as perceived by Jordanian medical students studying at Jordan University of Science and Technology. Methods. The present work is a cross-sectional questionnaire-based study. First-, second-, and third-year medical students were invited to complete an anonymous questionnaire. Students’ responses were numerically coded, and the results were analyzed to reveal any statistically significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 36 publications
5
72
0
Order By: Relevance
“…Individual and environmental factors were both significant in the user's acceptance of YouTube for learning [20]. Perceived usefulness was an important factor for the anatomy students in Jordan, affecting their decisions to use YouTube as their learning resources [11]. The key conclusion from this finding was that although the critical period of Covid-19 pandemic forced more teachers and students to shift their T&L activities either in full or part, they could not ignore these three factors to guarantee the students' acceptance of online resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual and environmental factors were both significant in the user's acceptance of YouTube for learning [20]. Perceived usefulness was an important factor for the anatomy students in Jordan, affecting their decisions to use YouTube as their learning resources [11]. The key conclusion from this finding was that although the critical period of Covid-19 pandemic forced more teachers and students to shift their T&L activities either in full or part, they could not ignore these three factors to guarantee the students' acceptance of online resources.…”
Section: Discussionmentioning
confidence: 99%
“…In a study among students of an English class, learning on YouTube was found to be more flexible, interesting, and interactive; thus, integrating YouTube videos from language-teaching Youtubers into T&L activities would be useful to the students [10]. Educators are also encouraged to create videos and upload them on YouTube to improve the learning experiences of their students [11].…”
Section: Benefits Of Youtube Videos As a Learning Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical students have successfully learned anatomical subjects with the help of YouTube (Mustafa et al, 2020). The author noted that students were very optimistic about using YouTube videos as they enhance understanding, memorisation, and retention of factual anatomical knowledge.…”
Section: Blending By Youtube Videos As Learning Activitymentioning
confidence: 99%
“…Valdez Mayo R, Coquia Adrillana C, Casil Cruz A, Andrada Fernandez Jr. D, Veasuvalingam B MedEdPublish https://doi.org/10.15694/mep.2021.000046.1 Mustafa et al, 2020). Nevertheless, video tutorials on cadaveric tools or models carried out by anatomy educators can supplement students with assured material accuracy (Barry et al, 2016).…”
Section: Blending By Youtube Videos As Learning Activitymentioning
confidence: 99%